2019
DOI: 10.3390/ijerph16040587
|View full text |Cite
|
Sign up to set email alerts
|

From Science to Policy and Practice: A Critical Assessment of Knowledge Management before, during, and after Environmental Public Health Disasters

Abstract: Canada regularly faces environmental public health (EPH) disasters. Given the importance of evidence-based, risk-informed decision-making, we aimed to critically assess the integration of EPH expertise and research into each phase of disaster management. In-depth interviews were conducted with 23 leaders in disaster management from Canada, the United States, the United Kingdom, and Australia, and were complemented by other qualitative methods. Three topics were examined: governance, knowledge creation/translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 33 publications
0
65
0
1
Order By: Relevance
“…In the end, as Généreux et al noted, good governance is perhaps the single most important factor influencing the effectiveness of emergency preparedness, response, and recovery ( 149 ). With the existing research achievements, it is necessary for government and related organizations to reform policies, innovate practices, cultivate relationships, and share responsibility for ensuring the safety, health, and well-being of affected people.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…In the end, as Généreux et al noted, good governance is perhaps the single most important factor influencing the effectiveness of emergency preparedness, response, and recovery ( 149 ). With the existing research achievements, it is necessary for government and related organizations to reform policies, innovate practices, cultivate relationships, and share responsibility for ensuring the safety, health, and well-being of affected people.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…More surprising is the similar trend of high preparedness that was displayed concerning the knowledge of staff, as most healthcare workers do not often participate in MCIs involving hazardous materials. Building and sustaining a high level of knowledge concerning MCIs that result from toxicological/chemical materials has been found in varied healthcare systems to be complex [5,8]. One possible explanation for this phenomenon is the accessibility of data that characterizes the Israeli acute-care hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 11 September 2001 attack in the USA, the interest of governing authorities, as well as of the media and the public, expanded to include chemical and toxicological threats [6]. Many states invest significant resources in building their capacity to manage such events and mitigate their consequences, but nonetheless, it has been stated that such efforts have been too limited and, as of yet, many deficiencies in the level of emergency preparedness are still predominant [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Experience from these activities has suggested a clear need for guidance on developing MHPSS programming from a DRR perspective. Moreover, research has indicated that academic actors may be more familiar with concepts of the Sendai Framework than practitioners [3] and that significant knowledge gaps exist in approaches to managing MHPSS programming across emergency phases [4]. Therefore, the WHO initiated a three-year project to develop and test practical guidance and curriculum for psychosocial support preparedness in selected countries.…”
Section: Introductionmentioning
confidence: 99%